RSUD WATES MEDICAL PERSONNEL PERFORMANCE: WORKING ENVIRONMENT, WORKING STRESS, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - Asih, Endah Wiji; Kusmaryati Dwi (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2024)
The study was conducted on a sample of 120 employees of 500 medical staff at Wates Regional General Hospital, Yogyakarta. The purpose of the research is to identify factors that influence their performance. Samples are done using random stratified. Data analysis method using Multi Linear Regression. Research results show that the working environment and Organizational Citizenship Behavior have a positive influence on employee performance. A unique finding is that work stress has a positive impact on employee performance.